Membuka Pintu Hiburan di Era Kolonial: Sejarah Perkembangan Bioskop di Batavia, 1900-1942 - Agustin, Nurmalia; Ismawati, Deby Ayu; Fauziah, Mustasyifa (Warisan: Journal of History and Cultural Heritage, 2023)
This research aims to discuss the history of cinema in Batavia from entertainment before the existence of cinemas, the background of the beginning of cinemas to Chinese involvement in the cinema industry. Of course, in the past, watching in theaters already existed during the Dutch colonial period. Movie theaters have existed in Batavia since 1900. The culture of watching this movie began to enter in the early 20th century where the indigenous people at that time called the moving image "Ideop Picture". The method used in this research is the historical method in which there are heuristics, internal and external criticism, interpretation, and historiography. From the results of this study, it is hoped that it can provide insight to the public about the history of cinema, not only exist to be enjoyed at this time but also can be remembered and remembered how the history of cinema in Batavia opened the gateway to entertainment in Indonesia.